(untitled) (La Aljaba. Segunda Época. Revista de Estudios de la Mujer, 2024)
The treatment of justice under the Austrians has entailed significant and abundant contributions. In this article we propose to approach the various historiographic contributions in this regard: Social Cultural History, Social History of Law, New Political History, Women’s History and Gender Studies. Legal studies, we understand, must be approached from a new conception influenced by the contributions of the historiographical perspectives mentioned above.